CD19+ lineage chimerism, an early biomarker after anti-CD19 CAR-T cell therapy in patients previously receiving a hematopoietic stem cell transplantation - Martínez-Romera, Isabel; Galán-Gómez, Víctor; González-Martínez, Berta; Guerra García, Pilar; San Román Pacheco, Sonsoles; Corral Sánchez, Dolores; Mozo del Castillo, Yasmina; Bueno Sánchez, David; Sisinni, Luisa; González Guerrero, Alba; Castellano Dámaso, Serafin; Sánchez Zapardiel, Elena; et al. (Frontiers in Immunology, 2022)
Treatment targeting CD19 by a chimeric antigen receptor expressed on T cells (anti-CD19 CAR-T) has led to a breakthrough in the management and treatment of relapsed and refractory B- cell acute lymphoblastic leukemia (B-ALL). After infusion, the efficacy of anti-CD19 CAR-T is monitored by bone marrow negative minimal residual disease and the absence of peripheral CD19+ B lymphocytes (B-cell aplasia). In patients who have received an allogenic Hematopoietic Stem Cell Transplantation (HSCT) prior to treatment with anti-CD19 CAR-T, monitoring lineage-specific chimerism could be helpful. We found that on 4 patients who received anti-CD19 CAR-T cells after HSCT and achieved early complete response, CD19+ lineage mixed chimerism but not CD3+ lineage mixed chimerism monitored by molecular techniques anticipated earlier than B-cell aplasia determined by flow cytometry, lack of effectiveness of anti-CD19 CAR-T and leukemia relapse. Donor lymphocyte infusions (DLIs) did not prevent relapse but recovered CD3+ full donor chimerism. We suggest that continuous lineage chimerism analysis should be done routinely in patients who receive anti-CD19 CAR-T cells after HSCT and achieve complete remission because it can support early treatment intervention. However, the role of DLI in this setting is unclear, so further prospective studies should be developed.